Series interconnects and charge extraction interfaces for hybrid solar cells - Hey, AS (2013)
This thesis investigates novel hole extraction interfaces and series interconnects for applications in organic photovoltaics, specifically in single junction solid-state dye-sensitized solar cells (DSSCs) and tandem DSSC/polymer bulk heterojunction solar cells. Improvements in hole extraction and device performance by using materials compatible with scalable deposition methods are presented, including tungsten- and molybdenum-disulphide (WS2 and MoS2), and p-type doped spiro-OMeTAD (2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene) nanoparticle dispersions. WS2 and MoS2 hole extraction layers increase averaged short circuit currents by 20% and 16% respectively, and power conversion efficiencies by 19% and 14% respectively when compared with control devices. Similarly, doped spiro-OMeTAD nano-particle layers improved short circuit current densities by 32% and efficiencies by 9%. Tandem device interconnects using these novel hole extraction formats have been fabricated, but although devices did exhibit rectification, overall performance was poor. Possible reasons for their limited success have been analysed. Dye-sensitized solar mini-modules are also reported. In order to assure the scalability of DSSC technology, these larger area devices were constructed using doctor blade coating to deposit the hole transporter material. As well as achieving a respectable maximum power conversion efficiency of 2.6%, it has also been shown that the extent to which hole transporter infiltrates the mesoporous photoanode of these devices may be tuned by altering substrate temperature during deposition. It was found that an optimal coating temperature of 70 degrees C produced the best efficiency, with a corresponding pore-filling fraction of 41%.